Mare’s milk: composition and protein fraction in comparison with different milk species - Krešimir Kuterovac; Vesna Gantner; Klemen Potočnik; Angela Cividini (Mljekarstvo)
The usage of the mare’s milk as functional food especial for children intolerant to cow’s milk, with neurodermitis, allergies and similar disorders desiring to improve the quality of life is fiercely debated for last decades but there were no scientific studies to suggest such use of mare’s milk based on scientific research. The objectives of this study were to determine similarities of mare’s milk in comparison with milk of ruminants (cattle, sheep and goat) and human milk in terms of milk composition and protein fraction as whey proteins, caseins and micelles size. All differences were discussed regarding usage of mare’s milk in human diet and compared to milk which is usually used in human nutrition. Regarding composition, the mare’s milk is similar to human milk in of crude protein, salt and lactose content, but it has significantly lower content of fat. Fractions of main proteins are similar between human and mare’s milk, except nitrogen casein (casein N) which has twice lower content in human than in mare’s milk. Content of casein N from all ruminants’ milk differ much more. Just for true whey N and non-protein nitrogen (NPN) similar content as human and mare’s milk has also goat milk. The casein content is the lowest in human milk; this content is three times greater in mare’s milk and six to seven times greater in goat’s and cow’s milk, while in sheep’s milk it is more than 10 times grater. In many components and fractions mare’s milk is more similar to human milk than milk of ruminants. A detail comparison of protein fraction shows quite large differences between milk of different species. More study and clinical research are needed that can recommend usage of mare’s milk in human diet as functional food on scientific bases.